A general life estimation method for overhead conductors based on fretting fatigue behavior of wires. (October 2022) - Rocha, P.H.C.; Langlois, S.; Lalonde, S.; Araújo, J.A.; Castro, F.C.
Highlights: A novel methodology for predicting fatigue life of overhead conductors based on damage similitude between conductor's wires and fretting fatigue tests on wires. Good agreement between life predictions and observed number of cycles to failure has been noticed for the AAAC 900 MCM conductor. Accurate predictions of critical damage regions in comparison with experimental observations. The fretting fatigue data of AA6201-T81 wires can be reduced to a single stress-life curve described by the SWT model. Experimental strain measurements on critical wires of the conductor shows an appropriate precision of the FE model on the computation of strain. Abstract: This work proposes a new methodology to assess the fatigue life of overhead conductors. The approach relies on (i) a global stress analysis of a multistranded conductor using a 3D finite element (FE) beam-to-beam contact model and (ii) a local fatigue damage analysis of the wires that exploits the similitude concept of the S-N method. The methodology can be applied to general conductor-clamp assemblies and provide predictions about the fatigue life and the critical regions of failure of conductors. The effectiveness of the methodology is demonstrated using experimental data of an AAAC 900 MCM conductor obtained in a resonant fatigue testing bench. Different levels of tension loads and bending displacement amplitudes were considered in the assessment. Experimental strain measurements show that the conductor-clamp FE model can compute the stress distribution along the critical region of failure of the conductor with satisfactory accuracy. New fretting fatigue data together with literature data of AA6201-T81 wires are used to demonstrate that the stress-based version of the Smith–Watson–Topper model can reasonably describe the fatigue behavior of these aluminum wires and hence is used as fatigue parameter to predict the fatigue behavior of the AAAC 900 MCM. The predicted critical regions of failure and fatigue lives of the conductor-clamp assembly were in good agreement with the experimental observations. The level of accuracy obtained is acceptable for engineering calculations, indicating that the methodology can be a promising fatigue analysis tool for overhead conductors.